A deeper mining on the protein composition of VA-MENGOC-BC®: An OMV-based vaccine against N. meningitidis serogroup B and C - Yordanka Masforrol; Jeovanis Gil; Darien García; Jesús Noda; Yassel Ramos; Lázaro Betancourt; Osmany Guirola; Sonia González; Boris Acevedo; Vladimir Besada; Osvaldo Reyes; Luis Javier González (Taylor & Francis Group, 2017)
The protein composition of an Outer Membrane Vesicle (OMV) preparation that constitutes the active pharmaceutical ingredient of VA-MENGOC-BC®, an effective vaccine against Neisseria meningitidis serogroups B, and C is presented. This preparation has a high lipid content and five abundant membrane proteins (FetA, PorA, PorB, RmpM, and Opc), constituting approximately 70% of the total protein mass. The protein composition was determined by combining the use of the Hexapeptide Ligand Library and an orthogonal tandem fractionation of tryptic peptides by reverse-phase chromatography at alkaline and acid pH. This approach equalizes the concentration of tryptic peptides derived from low- and high-abundance proteins as well as considerably simplifying the number of peptides analyzed by LC-MS/MS, enhancing the possibility of identifying low-abundance species. Fifty-one percent of the proteins originally annotated as membrane proteins in the genome of the MC58 strain were identified. One hundred and sixty-eight low-abundance cytosolic proteins presumably occluded within OMV were also identified. Four (NadA, NUbp, GNA2091, and fHbp), out of the five antigens constituting the Bexsero® vaccine, were detected in this OMV preparation. In particular, fHbp is also the active principle of the Trumenba® vaccine developed by Pfizer. The HpuA and HpuB gene products (not annotated in the MC58 genome) were identified in the CU385 strain, a clinical isolate that is used to produce this OMV. Considering the proteins identified here and previous work done by our group, the protein catalogue of this OMV preparation was extended to 266 different protein species.